EVALUASI SISTEM MANAJEMEN SUMBER DAYA MANUSIA PADA PENEMPATAN KERJA PETUGAS DI UPT PUSKESMAS MALINGPING - Mita Melisa Febriani; Syamsul Hidayat; Saepudin Saepudin (Universitas Bina Bangsa, 2021)
One of the important resources in management is human resources. The importance of human resources needs to be realized by all levels of management. However advanced technology is today, the human factor still plays an important role for the success of a Puskesmas. The study aims to evaluate the HR management system in planning, organizing, directing, and contolling the work placement of officers at Puskesmas Malingping. The type of research used in the research is qualitative fenomenology research, namely observation, in-depth interviews and documentation. The resuls showed that the Puskesmas Malingping reports the shortage to the health office by looking at the vacancies in the health center. Health workers, midwives and nurses who do not have competence in the fields of management, UKP Pharmachy and laboratory analysis are forced to fill the vacancies in these sections due to a lack of manpower. The conclusion of this researcher shows that the human resource management system at the puskesmas Malingping four aspects, namely planning, organizing, directing and controlling and its evaluation shows that the human resource management system in work placements at the puskesmas Malingping has not been maximized due to the lack of health works resulting in placement work that is not in accordance with the disiplince of science